PRODUCTION AND QUALITY ENHANCEMENT OF MANGO USING FAN JET SPRAYER IRRIGATION TECHNIQUE - Nani Heryani; Budi Kartiwa; Yayan Apriyana; Haris Syahbuddin (Indonesian Journal of Agricultural Science, 2016)
Lack of water in reproductive phases (flowering, fruit formation and maturation) of mango can reduce fruit production and quality. In these phases the plant must be protected from water stress. The aim of the research was to assess the effect of irrigation on the productivity and quality of mango fruits. The study was conducted at the Cukurgondang Experimental Station, Pasuruan, East Java, from April to December 2013, using 40 mango trees of 21 year-old Arumanis variety. Mangoes were planted on five rows with eight plants for each row and 6 m x 6 m spacing within the row. Fan jet sprayer irrigation was installed using hose according to plant diameter. The irrigation technique of fan jet sprayer with four nozzles per plant was applied at 125, 100, 75, 50 and 0% of crop water requirements or equal to 828, 663, 497, 331 and 0 liters of water per tree, every seven days. The parameters observed were the number and weight of fallen fruits and the number, weight and quality of mangoes harvested. The results showed that irrigation of 50% and 75% of crop water requirement had the highest and lowest number of fallen fruits (26% and 14% of total production), respectively. The highest and lowest total number of mangoes were 3.108 and 1904 fruits, respectively, which were achieved at irrigation of 50% and 75% of crop water requirement. Further, the highest and lowest total weight of mango fruits were 1036.2 and 677.9 kg respectively which were achieved at irrigation of 50% and 125% of crop water requirement. Mango fruits produced were dominated by grades 2 and 3 with A quality.